Etiologic Role of Infectious Agents - Chen, Edward S.; Moller, David R. (Seminars in Respiratory and Critical Care Medicine, 2014)
A consensus statement found in most peer-reviewed literature on sarcoidosis is that the etiology of sarcoidosis is unknown. It is timely to review whether this statement should be revised. Many infectious agents meet the basic requirements of inducing granulomatous inflammation and immunologic responses consistent with sarcoidosis including oligoclonal expansion of CD4+ T cells, polarized Th1 and possibly Th17 responses, and dysregulated regulatory T-cell function. Studies over the past decade provide increasing and complementary data to implicate a role for infectious agents in sarcoidosis etiology. These studies used different methodologies such as polymerase chain reaction and mass spectrometry to document microbial nucleic acids and proteins in sarcoidosis tissues. Multiple studies report antigen-specific immune responses to specific microbial proteins in sarcoidosis. In aggregate, these studies provide compelling evidence that mycobacteria play a major etiologic role in sarcoidosis in the United States and Europe. Studies from Japan support a role for Propionibacteria as a major etiologic agent in the country. There is controversy over how these (or other) infectious agents cause sarcoidosis. The hypothesis that chronic sarcoidosis is caused by a viable, replicating mycobacterial or other infection has no direct pathologic, microbiologic, or clinical evidence. A novel hypothesis links microbial triggers to a sarcoidosis outcome from the accumulation of aggregated proinflammatory serum amyloid A within granulomas, providing a mechanism for chronic disease in the absence of any viable tissue infection. Further studies are needed to provide more definitive evidence for these competing hypotheses before the statement that the etiology of sarcoidosis is unknown becomes obsolete.
Keywords: sarcoidosis; Th1 immunity; mycobacteria; Propionibacteria; serum amyloid A